2016
DOI: 10.1109/tmm.2016.2597001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Video Delivery in m-Health Emergency Applications

Abstract: M-health services are expected to become increasingly relevant in the management of emergency situations by enabling real-time support of remote medical experts. In this context, the transmission of multiple health-related video streams from an ambulance to a remote hospital can improve the efficacy of the teleconsultation service, but requires a large bandwidth to meet the desired quality, not always guaranteed by the mobile network. In order to deliver the multiple streams over a single bandwidth-limited wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It was also common to find environmental sensors to monitor ambient conditions at the emergency location. The reported ambient conditions were temperature, light, noise, and humidity [ 10 , 11 , 20 , 24 ]. In terms of sensor data sampling, authors in [ 8 ] reported AN error-free transmission of biomedical signals.…”
Section: Resultsmentioning
confidence: 99%
“…It was also common to find environmental sensors to monitor ambient conditions at the emergency location. The reported ambient conditions were temperature, light, noise, and humidity [ 10 , 11 , 20 , 24 ]. In terms of sensor data sampling, authors in [ 8 ] reported AN error-free transmission of biomedical signals.…”
Section: Resultsmentioning
confidence: 99%
“…Researches on adaptive streaming have been mostly applied to video context, and generally range from network coding, bandwidth detection, and rate determinations [2], [3], [4], [5], [6] to quality of service and user experience [7], [8], [9]; many also have been applied to video-based tele-medicine systems [10], [11], [12], [13], [14], [15]. In [13], [14], and [15] for instance, the authors study bandwidth adaptation techniques for adaptive transmission of medical videos over the bandwidth-limited mobile networks, some targeting 4G and beyond small cells. Also, the authors in [16] target lower network layers in mobile tele-medicine, and propose a TDMA-based MAC layer scheme for bandwidth reservation among cells for tele-medicine traffic handoff.…”
Section: A Dynamic Adaptive Streamingmentioning
confidence: 99%
“…Recent research efforts on different types of networks include [10][11][12][13], which focus on the problem of medical video streaming over 4G cellular networks, as well as [14], which proposes a framework for transmitting medical multimedia over cognitive radio networks.…”
Section: Related Workmentioning
confidence: 99%
“…The authors point out, however, that AVC (which is used in our work) provides better picture quality. The work in [12], which focuses on cellular networks, also uses SVC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%